Potential overtreatment in elderly patients with diabetes mellitus: Results from a cross-sectional study in German general practice - Solveig Weise; Christiane Oelschläger; Susanne Unverzagt; Jens Abendroth; Marcus Heise; Thomas Frese (European Journal of General Practice)
Background It is important for general practitioners (GPs) to protect elderly patients with diagnosis of diabetes type 2 (DM2) from overtreatment.Objective To analyse the metabolic control and treatment of elderly patients with DM2 in general practices.Methods This cross-sectional study involved 46 general practices in a federal state of Germany. Inclusion criteria for patients were diagnosis of DM2, age of 70 years or above, no palliative care and at least one practice contact within the last six months. A study nurse randomly selected 10 eligible patients and extracted data on haemoglobin A1c (HbA1c), diabetes treatment, secondary prevention and GP’s characteristics. Risk of overtreatment was defined as having a HbA1c <47.5 mmol/mol (6.5%) and receiving glucose-lowering drugs, and overtreatment as being at risk of overtreatment and being aged 80 years or above or living in a nursing home.Results Among 460 participants, 36.0% received oral-antidiabetic drugs, 16.7% insulin, 16.2% both and 31.1% received diet/exercise. Overtreatment occurred in 12% of elderly patients with DM2, risk of overtreatment in 24%. Overtreatment was significantly associated with urban residency (OR 2.17). Female elderly patients with DM2 were significantly less often at risk of overtreatment (OR 0.59). Cluster effects were evident between general practices’ treatment and monitoring of elderly patients with DM2 in quantitative data.Conclusion Overtreatment is a relevant problem in elderly patients with DM2 for which GPs should regularly check and start deprescribing. Cluster effects suggest heterogeneity between general practices in diabetes management and monitoring.